Halloween II. [videorecording (DVD)] - Rosenthal, Rick, 1949-; Curtis, Jamie Lee, 1958-; Pleasence, Donald (Shout! Factory, 2012)
Picking up exactly where its predecessor left off, follows 'boogeyman' Michael Myers as he stalks the deserted halls of the hospital where his intended victim lays waiting. Meanwhile, his doctor desperately continues to hunt him down.